Perancangan Sistem Informasi Pendaftaran Siswa Baru di SMK YASTRIF 1 Parung Panjang Berbasis Web - Ismi Ismi; Ratna Willis; Siti Soliah; Iyus Tiawati; Yulianti Yulianti (Program Studi Teknik Informatika Universitas Pamulang, 2020)
In this millennial era, the development of technology has really sped up the difference compared to the previous era. Every day, even at the clock, there are always new developments in technology. Invarious fields, everything wants to be practical and fast, all of that cannot be separated from new discoveries from technology plus millennials who want everything instant and fast. People nowadays are almost all technology literate, one of which is the internet. Just by sitting pretty and connected to the internet, everything can be done without having to leave the house. Parents and school children don't have to bother queuing just to register for school, just open the internet, everything can be done at any time. This study aims to make it easier for new students who are millennials by building online media, namely websites using the HTML programming language, MySQL database. Prospective students only need to be connected to the internet and can register for schools and be more efficient.